Pengembangan Minat Baca Siswa Berbasis Psikologi Pendidikan Islam di Sekolah Dasar - Mulyadi Mulyadi; Alef Theria Wasim; Arif Budi Raharjo; Fitriah M. Suud (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Abstract: Reading is opening the window of the world, finding lots of knowledge and opening up one's insights. So reading is the most important thing in education, but the fact is children's interest in reading, especially in Indonesia is still very minimal. This study aims to find out how parenting was developed by parents of students who excel at the As-Shafa Islamic Elementary School in Pekanbaru, Riau in increasing children's reading interest. The research method used in this study was qualitative phenomenology, data collection was carried out through interviews and interactive documentation in three components of analysis, namely data reduction, data presentation, and conclusions. The results obtained in the study that the majority of parents of outstanding students are busy working but still taking the time to give love, protection, guidance, accompany children in learning, direction and education in daily life. While the patterns found are mostly using democratic and situational patterns. This research suggests that parents maintain the quality of attachment with children and spend a lot of time in accompanying them to learn.